Race, Nation and Gender in Modern Italy Intersectional Representations in Visual Culture - Giuliani, Gaia (Mapping Global Racisms,, 2019)
This book explores intersectional constructions of race and whiteness in modern and contemporary Italy. It contributes to transnational and interdisciplinary reflections on these issues through an analysis of political debates and social practices, focusing in particular on visual materials from the unification of Italy (1861) to the present day. Giuliani draws attention to rearticulations of the transnationally constructed Italian 'colonial archive' in Italian racialised identity-politics and cultural racisms across processes of nation building, emigration, colonial expansion, and the construction of the first post-fascist Italian society. The author considers the 'figures of race' peopling the Italian colonial archive as composing past and present ideas and representations of (white) Italianness and racialised/gendered Otherness. Students and scholars across a range of disciplines, including Italian studies, political philosophy, sociology, history, visual and cultural studies, race and whiteness studies and gender studies, will find this book of interest.